Advanced Post‐Potassium‐Ion Batteries as Emerging Potassium‐Based Alternatives for Energy Storage. (9th September 2020) - Yao, Qianqian; Zhu, Changbao
Abstract: Potassium‐based batteries are considered attractive alternatives for lithium ion batteries, particularly for large‐scale energy storage, owing to their economic value and abundance. There have been significant achievements in the extensive investigations of potassium‐ion batteries (PIBs). However, post‐potassium‐ion batteries (post‐PIBs), including potassium–sulfur (K–S), potassium–selenium (K–Se), all‐solid‐state potassium‐ion batteries (ASSPIBs), and aqueous potassium‐ion batteries (APIBs) along with their respective advantages such as higher energy density, better safety, lower costs, and higher power density, are still in the initial stages of research and require further attention. Therefore, this review summarizes the recent progress, current challenges, and advancements in post‐PIBs such as K–S/Se batteries and ASSPIBs. Additionally, the challenges and solutions of using K metal in such systems are discussed. Thereafter, smart designs for electrodes and electrolytes, along with rational constructions for obtaining desirable APIBs are evaluated. Finally, the development trends, challenges, and prospects are estimated for advanced post‐PIBs. This review provides instructive guidelines for research and development of promising potassium‐based systems, in particular, further application of post‐PIBs. Abstract : Post‐potassium‐ion batteries (post‐PIBs), as emerging and economic alternatives, have garnered significant attention and achieved rapid development. The recent progress, challenges, and solutions for post‐PIBs, including potassium‐sulfur/selenium batteries, all‐solid‐state potassium‐ion batteries, aqueous potassium‐ion batteries, and K metal anodes, are discussed. In addition, instructive guidelines and perspectives for the future development of post‐PIBs are provided as well.